Beneficial effects of Vigna angularis extract in osteoporosis and osteoarthritis. Issue 12 (20th October 2020) - Lim, Hyung Jin; Park, Sang‐Ik; Bak, Seon Gyeong; Cheong, Sun Hee; Lee, Soyoung; Baek, Young‐Bin; Lee, Chang‐Min; Lee, Kang Min; Lee, Seung Woong; Lee, Seung‐Jae; Rho, Mun‐Chual
Abstract: In Asia, Vigna angularis (azuki bean) has been used as a traditional medicine to treat various diseases because of its biological properties. Osteoarthritis (OA) and osteoporosis (OP) are common regenerative bone diseases that are characterized by deterioration of joint and bone structure. In this study, we evaluated the effects of Vigna angularis extract (VAE) on monosodium iodoacetate (MIA)‐induced OA and ovariectomy (OVX)‐induced OP models. In the MIA‐induced OA results, severe OA was alleviated by the administration of VAE. Extensive local damage in the cartilage and hemorrhagic and edematous of surrounding tissues were decreased by VAE treatment. Articular cartilage was almost intact except for a focal mild abrasion, and the surface was glistening, similar to that of the normal joint. In the OVX‐induced OP results, bone mineral content (BMC) and bone mineral density (BMD) were recovered by VAE treatment, and it improved the microstructures of bone. These results show that VAE could inhibit OA and OP symptoms. Abstract : We investigated the regulatory effects of bone diseases of ethanolic extract from Vigna angularis (azuki bean). Vigna angularis (azuki bean) could be serve as natural bone‐regulatory material.